PERAN PEMERINTAH DALAM PEMULIHAN EKONOMI UMKM DALAM SEKTOR TEKNOLOGI (PADI UMKM) - DJIHADUL MUBAROK; DARU SUSANTI (Develop: Jurnal Ekonomi Pembangunan, 2020)
The problem raised in this research is how the role of the government in the economic recovery of UMKM in Indonesia during the Covid-19 pandemic in the technology sector (PaDi UMKM) and the concept used on the platform with the research method used is qualitative research which is library research, this research is obtained by conducting studies that come from research, books, news and statistical data about information on PaDi UMKM.